Want a healthy life: A qualitative study on motivation to Cease alcoholic drink addiction - Ibnu Sutoko; Latipun Latipun (Journal of Social Behavior and Community Health, 2021)
Background: The alcoholic drink level of consumption is still high, particularly among adolescents and adults. Continuous consumption of alcoholic drinks can lead to addiction, making it difficult to cope with; however, some individuals with such a situation are could cease the habit. This study aims to explore the process of individuals breaking away from alcohol dependence. Methods: The research approach used qualitative with a phenomenological design. Semi-structured interviews were conducted to obtain in-depth data from eight subjects selected according to purposive sampling criteria. The data was analyzed using a descriptive phenomenological method. Results: The study results found four main themes for quitting alcoholic beverages: the influence of the experience of becoming an addict, a strong internal desire to quit, being threatened by biological impacts, internal and external driving factors to quit. Conclusion: Based on the findings, individuals who want to quit addiction must have a strong desire, consider the biological impact on health and have internal and external driving factors.